2016
DOI: 10.1021/acscatal.6b00937
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Migration of Oxygen Vacancies in SrCoO3 and Their Effect on Oxygen Evolution Reactions

Abstract: Perovskite SrCoO 3 is a potentially useful material for promoting the electrocatalytic oxygen evolution reaction, with high activities predicted theoretically and observed experimentally for closely related doped perovskite materials. However, complete stoichiometric oxidation is very difficult to realize experimentally -in almost all cases there are significant fractions of oxygen vacancies present. Here, using first principles calculations we study oxygen vacancies in perovskite SrCoO 3 from thermodynamic, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 47 publications
5
93
0
Order By: Relevance
“…This differs from the undoped case of SrCoO 3 where the two electrons tend to localize on neighbouring Co sites. [35] It has been shown that the vacancy formation energy correlates with the p-band centre, such that either of which could be used as an activity descriptor [16,52]. This correlation also holds for the structures considered here.…”
Section: Srsc X Nb Y Co 1-x-y O 3 : Distributions and Structuressupporting
confidence: 51%
See 3 more Smart Citations
“…This differs from the undoped case of SrCoO 3 where the two electrons tend to localize on neighbouring Co sites. [35] It has been shown that the vacancy formation energy correlates with the p-band centre, such that either of which could be used as an activity descriptor [16,52]. This correlation also holds for the structures considered here.…”
Section: Srsc X Nb Y Co 1-x-y O 3 : Distributions and Structuressupporting
confidence: 51%
“…The increased oxygen vacancy formation energy for low Sc and Nb doping fractions maintains a near stoichiometric concentration of oxygen ions. Our earlier work has revealed a detrimental role of surface oxygen vacancies on the OER activity in SrCoO 3 [35]. Hence, minimizing oxygen vacancy concentrations can be expected to help minimize the overpotential for OER.…”
Section: Srsc X Nb Y Co 1-x-y O 3 : Distributions and Structuresmentioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, we demonstrate control over the spatial arrangement of oxygen vacancies in an oxide crystal, which we and others have shown to be useful in modulating electronic, magnetic, and catalytic behaviors. [36][37][38][39] By employing different arrangements of CoO x and TiO 2 layers under the same epitaxial strain and growth conditions, the Co oxidation state can be raised from the nominal +3 found in brownmillerite SrCoO 2.5 to +3.25 and +3.5 in (SrCoO 2.64 ) 2 : (SrTiO 3 ) 1 and (SrCoO 2.76 ) 1 : (SrTiO 3 ) 1 superlattices, respectively. The results illustrate how interface engineering can be combined with defect control to achieve novel properties in complex oxides.…”
Section: -4mentioning
confidence: 99%